The Age-Specific Impact of Cellular Immunity on Long-Term Outcome after Acute Coronary Syndrome - Kazem, Niema; Hofer, Felix; Koller, Lorenz; Hammer, Andreas; Hengstenberg, Christian; Niessner, Alexander; Sulzgruber, Patrick (Thrombosis and Haemostasis, 2021)
Background Personalized risk stratification after acute coronary syndrome (ACS) remains a challenging field in the aging society. Easily applicable strategies for risk prediction of adverse events from an age-specific perspective are needed. Considering the association of cellular immunity with coronary vessel disease, these cell lines mirror a reasonable value for risk assessment. Therefore, we aimed to elucidate the prognostic value of cellular immunity on long-term outcome after ACS from an age-specific perspective.Methods Patients presenting with ACS at the Vienna General Hospital admitted between December 1996 and January 2010 were enrolled within a clinical registry including standardized assessment of peripheral blood samples and immune phenotyping. Cox-regression hazards analysis was performed to elucidate the impact of cellular immunity on survival.Results A total of 832 patients were included within the final analysis and stratified according to age into individuals <65 years (n = 416) and ≥65 years (n = 416). After a median follow-up time of 8.6 years, a total of 516 (62.0%) individuals died. We found that the fraction of lymphocytes (adjusted hazard ratio [HR] of 0.61 [95% confidence interval, CI: 0.45–0.82]; p = 0.001), the fraction of neutrophil granulocytes (adjusted HR of 5.01 [95% CI: 1.62–15.46]; p = 0.005), and the neutrophil-to-lymphocyte ratio (NLR; adjusted HR of 1.47 [95% CI: 1.16–1.87]; p = 0.002) showed a strong and independent association with mortality in individuals ≥65 years. Notably, there was no effect on outcome observed for any of the tested cell lines in patients <65 years.Conclusion The present investigation highlighted a strong and independent age-specific effect of both the fraction of neutrophil granulocytes and lymphocytes as well as the NLR on outcome. Considering an age-dependent risk stratification, these routinely available values can be easily used to identify patients at risk for fatal events and contribute to proper secondary prevention after ACS.
Keywords: immunity; coronary syndrome; inflammation